Emergency Environmentalism: On Fear, Lifestyle Politics and Subjectivity - Crawford, Kate (Angelaki: Journal of Theoretical Humanities, 2009)
The Ziggurat stretches up into the Dubai skyline, a gigantic city in the shape of a pyramid. At a total of 2.3 square kilometres, the structure is vast – able to contain one million residents within its reinforced glass walls. Transport within the Ziggurat is via a networked public system that runs both horizontally and vertically, carrying people to all the reaches of the tightly contained city. Facial recognition technology functions as a city-wide security device, so no one need fear losing their keys. Above all, the Ziggurat is designed as a carbon neutral super structure: an eco pyramid that is capable of operating entirely off the grid, using wind, steam turbines and other natural sources of power. Both public and private spaces function as agricultural opportunities, and residents can be comfortable in the knowledge that they are living in the sustainable city of the future.